STRATEGI KOMUNIKASI DIGITAL MEDIA OFFICER CITY CENTRUM MALL DI KOTA SAMARINDA DALAM MENGELOLA INSTAGRAM @CITY_CENTRUM - Azizah, Nayla; Rohmah, Ainun Ni’Matu (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study aims to determine the communication strategy carried out by the Digital Media Officer (DMO) of City Centrum Mall Samarinda in managing Instagram @city_centrum. The research method uses descriptive qualitative research with data sources obtained from literature studies and also field research, namely interviews, observation and documentation. The data analysis technique uses an interactive model by Miles and Huberman. The initial problem of this research is the lack of interaction with followers. In the results of this study, the DMO team has implemented five stages of communication strategies in managing the @city_centrum Instagram account. Research indicators show that the DMO team is conducting research for its Instagram management. However, the team did not observe a structured strategy. The Planning indicator shows that the team plans aspects of the communication strategy, but it is not structured and has no SOP. The Implementation indicator proves that the content is not focused in accordance with the objectives of @city_centrum as brand awareness, lack of mutual communication. Evaluation Indicators show a team that evaluates every day and has KPIs but is not evaluated every content release. The Reporting indicator shows a team that makes written and unwritten reports, and the average percentage of @city_centrum account engagement is still below average. In conclusion, although the team has implemented all five stages of the communication strategy, it is still unstructured. The strategy should be made more structured.